Transumbilical Single-port Robotically Assisted Nipple-sparing Mastectomy: A Cadaveric Study. Issue 5 (May 2020) - Sarfati, Benjamin; Toesca, Antonio; Roulot, Aurélie; Invento, Alessandra
Abstract : Summary: The authors performed a transumbilical, single-port robotically assisted, nipple-sparing mastectomy on a cadaveric model to assess technical feasibility. Surgeon-controlled, robotic-wristed instrumentation, as well as 3-dimensional high definition (HD) vision allowed the entire dissection to be performed through a single incision placed in the umbilicus. The technique warrants further exploration and development before any application in clinical applied research.